A STEPWISE FRAMEWORK FOR PRIORITIZING BLOCKCHAIN-ENABLED WASTE MANAGEMENT STRATEGIES IN THAILAND USING FUZZY-AHP, FUZZY-PROMETHEE, AND FACTORIAL DESIGN APPROACH - Tepvarin, Apirak; Luangpaiboon, Pongchanun; Nanphang, Atiwat (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2025)
Waste management remains a significant challenge in Thailand, as over 27 million tons of waste are produced annually, with over 30% being inadequately managed. The absence of effective waste tracking and monitoring systems further exacerbates the severe environmental issues, such as water contamination, landfill emissions, and public health hazards, that result from this improper handling. This investigation investigates the potential of blockchain technology to improve the efficiency, security, and transparency of waste management processes. A structured decision-making approach is implemented to evaluate blockchain-enabled strategies, which integrates the Fuzzy Analytic Hierarchy Process (FAHP) and the Fuzzy Preference Ranking Organization Method for Enrichment Evaluations (FPROMETHEE). To ascertain the relative significance of the eight critical criteria—operational cost, environmental impact reduction, feasibility, long-term sustainability, revenue generation potential, landfill reduction, cost-effectiveness, and public accessibility—FAHP synthesizes expert opinions under uncertain conditions. Eight critical criteria were assessed. Four blockchain-based waste management strategies were examined: waste tracking systems, recycling incentive programs, waste exchange platforms (WEP), and pay-as-you-throw (PAYT) schemes. These strategies were ranked using the FPROMETHEE method, which ensured a standardized and robust evaluation through an optimization-based normalization procedure. Based on the results, PAYT is the most effective strategy, as it promotes accountability and minimizes landfill dependency by charging households based on waste volume, thereby incentivizing waste reduction at the source. The sensitivity analysis emphasizes WEP as an additional promising approach. PAYT and WEP demonstrate substantial economic viability, ecological impact, and advantages in transparency. The results underline the potential of blockchain to improve stakeholder collaboration, streamline waste management operations, and promote sustainable waste reduction initiatives. This research offers a practical framework for the implementation of blockchain-based waste management solutions to support Thailand's transition toward a circular economy, providing policymakers with valuable insights.